(untitled) (Docentes 2.0 Journal, 2024)
Artificial intelligence (AI) is advancing rapidly; based on the connectivity theory, a computer designed to interact with humanity solves certain tasks. The objective of the research was to analyze the impact of the application of artificial intelligence in teacher training. The research was framed in the cognitive paradigm, with a qualitative approach and a narrative design, through a documentary review and the PRISMA method. A search was conducted in various databases, and 11 relevant articles were selected. The results indicate that AI has the potential to improve teacher training by offering innovative tools and efficient pedagogical methods. Key dimensions such as cognitive, sensorimotor, emotional, and ethical demonstrate how AI facilitates autonomous learning, improves technical skills, and fosters interpersonal skills. However, limitations were evident, such as headteacher training’s need for more training and resistance to new technologies. The study suggests that AI can enrich teacher training and improve educational quality, but current barriers must be addressed to maximize its impact. Furthermore, it is recommended to investigate how AI influences teacher training and to consider greater geographical diversity in future studies.